AVALIAÇÃO DA CORROSIVIDADE DO BIODIESEL E MISTURAS EM AÇO POR ESPECTROSCOPIA DE IMPEDÂNCIA ELETROQUÍMICA - Viana, Fabiana Bernardes (2013)
The biodiesel tends to undergo changes in its composition over time making it corrosive. The materials in diesel engines are vulnerable to corrosion, especially aluminum, copper, cast iron and steel. In this study we evaluated the corrosion of carbon steel ABNT 1020 immersed in soy biodiesel (B100) and blends B4 and B5 using the technique of electrochemical impedance spectroscopy. To achieve a result more effectively, we used samples from microemulsions B100, B4 and B5 as a way to reduce the high resistivity of biodiesel. It was found with using this technique the exposed steel microemulsions of biodiesel and mixtures presented impedance modulus of about 3.75 (MEB4), 3.87 (MEB5) and 3.90 (MEB100) ohm.cmˉ¹, on low frequency (10ˉ¹ Hz), showing good corrosion resistance, especially for MEB100, which was also confirmed by the results of corrosiveness to copper and optical microscopy.